Pembinaan Tawanan Anak dalam Sistem Peradilan Pidana Sebuah Analisis untuk Rehabilitasi dan Reintegrasi Efektif - Achmad Ghozali Syafi’i (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to analyze and describe the pattern of fostering child prisoners in the criminal justice system. In many countries, including ours, there are children who are involved in law violations and have to serve time in detention. This research method uses a qualitative approach by collecting data through literature studies, policy research, and comparative analysis of child prisoner development programs that have been implemented in various countries. The research results illustrate that an effective coaching pattern for child prisoners is very important to help them in rehabilitation, reintegration and developing their potential. In this research, an analysis of various coaching approaches and programs implemented in various countries was carried out, as well as a review of relevant international standards. This research also considers important factors that influence the development of child prisoners, such as education, mental health, and family involvement. It is hoped that the results of this scientific work will provide a better understanding of effective child custody development patterns, as well as recommendations for improving existing practices.